1983
DOI: 10.1109/irps.1983.361958
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Electromigration Under Pulsed D.C. Conditions

Abstract: Aluminum thin films were stressed under constant and pulsed DC conditions. The pulsed tests were performed at a frequency of 1kHz and duty cycles of 25%, 50%, and 75%. A peak current density of 2 x 106 A/cm2 was used. To compare conductor lifetimes under constant and pulsed conditions and to determine the effect of current pulsing on the activation energy for electromigration, tests were performed from 1250C to 300'C. Thermal cycling, resulting from current pulsing, was minimized by testing whole, patterned wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…The average current density model has been correlated to the l / r 2 dependence of lifetimes [4]. This model assumes that the migrating atoms are influenced by an average current density, j,,, = T .…”
Section: Substrate Siodsimentioning
confidence: 99%
See 1 more Smart Citation
“…The average current density model has been correlated to the l / r 2 dependence of lifetimes [4]. This model assumes that the migrating atoms are influenced by an average current density, j,,, = T .…”
Section: Substrate Siodsimentioning
confidence: 99%
“…Reliability data and predictions for pulsedcurrent signals are typically based on dc measurements. For a pulsed dc current of duty cycle T , the pulsed-current lifetimes have been observed to be between 1," times greater [1]- [3] and l / r 2 times greater [4]- [6] than the dc lifetimes at equal dc and peak pulsed-current densities. Clearly, the accurate modeling of EM failure under pulsed-current stressing and correlation to dc lifetimes is required to better predict the reliability of IC's.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional EM work, this effective current is computed based on some assumed periodic current waveform. If the waveform is uni-directional, then Direct Current EM analysis is used, based on time-averaged current density (J avg ) [19].…”
Section: Effective-em Currentmentioning
confidence: 99%
“…This has resulted in very high current densities in wires which has made them susceptible to electromigration failures. Electromigration is the process of metal-ion transport due to high current density stress in metal and has been studied extensively [1][2][3]. As the metal-ions migrate, metal buildup or depletion occurs at locations in the wires where there is a divergence in the metal-ion flux.…”
Section: Introduction and Previous Workmentioning
confidence: 99%
“…During normal circuit operation, the signal interconnects in a VLSI design are actually stressed with pulsed DC currents, rather that with continuous DC currents. However, it has been shown that, in the absence of Joule heating, the mean time to failure of metal interconnect under pulsed DC currents can be expressed as a function of the average DC current [3][4] using Black's equation: [1], where A and n are empirically determined variables, j avg is the average current density, Q is the activation energy, and kT is the thermal energy. A simple approach to electromigration analysis therefore checks that each individual metal interconnect meets a specified mean time to failure.…”
Section: Introduction and Previous Workmentioning
confidence: 99%